2017
DOI: 10.33549/physiolres.933671
|View full text |Cite
|
Sign up to set email alerts
|

Vagal-Immune Interactions Involved in Cholinergic Anti-Inflammatory Pathway

Abstract: Inflammation and other immune responses are involved in the variety of diseases and disorders. The acute response to endotoxemia includes activation of innate immune mechanisms as well as changes in autonomic nervous activity. The autonomic nervous system and the inflammatory response are intimately linked and sympathetic and vagal nerves are thought to have anti-inflammation functions. The basic functional circuit between vagus nerve and inflammatory response was identified and the neuroimmunomodulation loop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 63 publications
0
37
0
4
Order By: Relevance
“…It was shown that AO supplementation, in contrast to standard treatment, improves HRV in DPU patients after H. pylori eradication. On the other hand, cholinergic effects of AO at systemic level, in turn, may also contribute to anti-inflammatory effects at the level of gastric mucosa [24,25] due to improvement of endothelial function and local blood flow that is known to have major effect on ulcer healing [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that AO supplementation, in contrast to standard treatment, improves HRV in DPU patients after H. pylori eradication. On the other hand, cholinergic effects of AO at systemic level, in turn, may also contribute to anti-inflammatory effects at the level of gastric mucosa [24,25] due to improvement of endothelial function and local blood flow that is known to have major effect on ulcer healing [45].…”
Section: Discussionmentioning
confidence: 99%
“…Since recently possible links between autonomic regulation and redox signalling are attracting attention of a growing number of researchers. The directions of these studies include anti-inflammatory effects of cholinergic (parasympathetic) signalling [24,25], interactions of adrenergic pathways with H 2 O 2 -mediated insulin signalling [26] and thermogenesis in adipose tissue [27]. It was reported recently that selective Nrf2 deletion in the rostral ventrolateral medulla evokes hypertension and "sympathoexcitation" in mice pointing out to close relationships of autonomic regulation and redox balance [28].…”
Section: Introductionmentioning
confidence: 99%
“…Activating α7nAChR by acetylcholine reduces the production and release of pro-inflammatory cytokines, such as TNF-α and IL-6, from the immune system. As a result, activating the anti-inflammatory reflex mechanism modulates the exaggeration of pro-inflammatory cytokine effects (Reardon 2016;Zila et al 2017;Chu et al 2020).…”
Section: Dear Editormentioning
confidence: 99%
“…Although no drug that can be clinically effective on α7nAChR with minor side effects in humans has been discovered yet, however, vagus nerve stimulation has been used for therapeutic purposes. It can improve sepsis, lung injury, rheumatoid arthritis, stroke, traumatic brain injury, obesity, diabetes, cardiovascular control, and pain management (Zila et al 2017).…”
Section: Dear Editormentioning
confidence: 99%
“…Vagal nerve has been identified to link to inflammatory response, its activity could suppress TNF-α and other pro-inflammatory cytokines. This anti-inflammation arc has been well-known as cholinergic anti-inflammation pathway [8]. Vagal nerve regulates inflammatory response through hypothalamicpituitary-adrenal axis, release of cortisol and vagovagal reflex [9].…”
Section: Introductionmentioning
confidence: 99%